Poor loading of major histocompatibility complex class II molecules with endogenously synthesized short peptides in the absence of invariant chain - Busch, Robert; Vturina, Iryna Y.; Drexler, Johannes; Momburg, Frank; Hämmerling, Günter J. (European journal of immunology, 1995)
In normal antigen-presenting cells, newly synthesized major histocompatibility complex (MHC) class II molecules associate with the invariant chain (Ii) glycoprotein in the endoplasmic reticulum (ER). They are loaded with peptides only after proteolytic removal of the Ii in post-Golgi endocytic vesicles. Since the Ii inhibits peptide binding to MHC class II molecules, this association could protect MHC class II molecules from being loaded with endogenous peptides early after biosynthesis. If this were an important function of the Ii in vivo, MHC class II molecules synthesized in cells lacking the Ii should be loaded efficiently with short endogenous peptides in the ER; such peptides are known to be present there due to TAP-mediated import from the cytosol. To examine this possibility, we have studied peptide loading in HeLa transfectants expressing murine H-2Ak MHC class II molecules either alone or together with an excess of Ii. Endogenous peptides could readily be extracted from conformationally intact Ak αβ dimers of biosynthetically labeled Ii+ cells, whereas peptide loading was greatly (> 95%) diminished in the absence of Ii. Significant amounts of sodium dodecyl sulfate-(SDS) stable 55-kDa peptide: Ak complexes were only found in the Ii+ transfectants. In the absence of Ii, the MHC class II molecules instead formed stable complexes with long (20 and 50 kDa) polypeptides. Known Ak-binding peptides bound stably to Ak molecules on Ii− cells, could be co-purified with them, and were resistant to release in SDS, suggesting that poor recovery of endogenous peptides was not due to decreased stability of Ak: peptide complexes in the absence of Ii. We conclude that protection of MHC class II molecules from endogenous short peptides does not appear to be a quantitatively important function of the Ii molecule, because peptide loading is inefficient in its absence.